The migratory bird treaty and a century of waterfowl conservation. Issue 2 (24th August 2017) - Anderson, Michael G.; Alisauskas, Ray T.; Batt, Bruce D. J.; Blohm, Robert J.; Higgins, Kenneth F.; Perry, Matthew C.; Ringelman, James K.; Sedinger, James S.; Serie, Jerome R.; Sharp, David E.; Trauger, David L.; Williams, Christopher K.
ABSTRACT: In the final decades of the nineteenth century, concern was building about the status of migratory bird populations in North America. In this literature review, we describe how that concern led to a landmark conservation agreement in 1916, between the United States and Great Britain (on behalf of Canada) to conserve migratory birds shared by Canada and the United States. Drawing on published literature and our personal experience, we describe how subsequent enabling acts in both countries gave rise to efforts to better estimate population sizes and distributions, assess harvest rates and demographic impacts, design and fund landscape‐level habitat conservation initiatives, and organize necessary political and regulatory processes. Executing these steps required large‐scale thinking, unprecedented regional and international cooperation, ingenuity, and a commitment to scientific rigor and adaptive management. We applaud the conservation efforts begun 100 years ago with the Migratory Bird Treaty Convention. The agreement helped build the field of wildlife ecology and conservation in the twentieth century but only partially prepares us for the ecological and social challenges ahead. © 2017 The Wildlife Society. Abstract : In 1916, the United States and Great Britain (on behalf of Canada) agreed, by treaty, to conserve the continent's migratory birds and set in motion many advances in wildlife science and conservation. We summarize a century of progress in waterfowl management and consider how this work positions us for the major social and ecological challenges ahead.